Crystal Structures of MBi2Br7 (M = Rb, Cs) - Filled Variants of AX7 Sphere Packing - Chang, Jen-Hui; Wolff, Alexander; Ruck, Michael (Zeitschrift für Anorganische und Allgemeine Chemie, 2016)
The reinvestigation of the pseudo-binary systems MBr-BiBr3 (M = Rb, Cs) revealed two new phases with composition MBi2Br7. Both compounds are hygroscopic and show brilliant yellow color. The crystal structures were solved from X-ray single crystal diffraction data. The isostructural compounds adopt a new structure type in the triclinic space group P1 . The lattice parameters are a = 755.68(3) pm, b = 952.56(3) pm, c = 1044.00(4) pm, α = 76.400(2)°, β = 84.590(2)°, γ = 76.652(2)°for RbBi2Br7 and a = 758.71(5) pm, b = 958.23(7) pm, c = 1060.24(7) pm, α = 76.194(3)°, β = 83.844(4)°, γ = 76.338(3)°for CsBi2Br7. The crystal structures consist of M+ cations in anticuboctahedral coordination by bromide ions and bromidobismuthate(III) layers 2∞[Bi2Br7]-. The 2D layers comprise pairs of BiBr6 octahedra sharing a common edge. The Bi2Br10 double octahedra are further connected by common vertices. The bismuth(III) atoms increase their mutual distance in the double octahedra by off-centering so that the BiBr6 octahedra are distorted. The CsBi2Br7 type can be interpreted as a common hexagonal close sphere packing of M and Br atoms, in which 1/4 of the octahedral voids are filled by Bi atoms. The structure type was systematically analyzed and compared with alternative types of common packings. The existence of a compound with the suggested composition CsBiBr4 could not be verified experimentally.
CRIS-Team Scopus Importer:2023-03-20
Keywords: CsBi; Hexagonal close AX; Hexagonal close AX; Ternary halides